2022
DOI: 10.1016/j.idcr.2022.e01401
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus jensenii mitral valve endocarditis: Case report, literature review and new perspectives

Abstract: Lactobacillus is a facultative anaerobic Gram-positive rod usually found in the normal microbiota of the gastrointestinal and genitourinary tract. Frequently dismissed as a contaminant, it is implicated in several diseases. We describe a rare case of endocarditis caused by Lactobacillus jensenii in an immunocompetent 40 year-old male patient , with a history of mitral valve repair. He presented complaining of asthenia and his laboratory results showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The retrospective studies of Arbarillo et al, Nwanyanwu et al, and Yelin et al [ 60 , 61 , 62 ] suggested that the true prevalence of infections caused by lactobacilli is higher than estimated only on the basis of case reports. In addition, in many of the reports analyzed here it was stated that lactobacilli are often disregarded as infective agents since they are considered culture contaminants [ 24 , 34 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The retrospective studies of Arbarillo et al, Nwanyanwu et al, and Yelin et al [ 60 , 61 , 62 ] suggested that the true prevalence of infections caused by lactobacilli is higher than estimated only on the basis of case reports. In addition, in many of the reports analyzed here it was stated that lactobacilli are often disregarded as infective agents since they are considered culture contaminants [ 24 , 34 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacilli were isolated from blood [ 15 , 16 , 17 , 18 , 20 , 21 , 22 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 49 , 52 , 55 , 56 , 57 ], diseased valve tissue [ 23 ], abscess fluids [ 48 , 51 , 52 , 54 , 57 , 58 ], cerebrospinal fluid (CSF) [ 46 ], marrow [ 30 ], arthrocentesis aspiration fluid [ 53 ] in anaerobiosis and, in some cases, also in aerobiosis [ 15 , 34 ]. Use of automated microbial detection system, i.e., BACT/ALERT 3D or the BACTEC systems (BioMérieux) with incubation at 35 °C were mentioned in some reports [ 23 , 31 , 34 ]. The case reports that described the identification procedures mostly referred to standardized instrumental techniqu...…”
Section: Cases Of Lactobacilli Infections Reported In Years 2019 2020...mentioning
confidence: 99%
See 3 more Smart Citations